Antimicrobial Activity from Putative Probiotic Lactic Acid Bacteria for the Biological Control of American and European Foulbrood Diseases - Massimo Iorizzo; Sonia Ganassi; Gianluca Albanese; Francesco Letizia; Bruno Testa; Cosimo Tedino; Sonia Petrarca; Franco Mutinelli; Alessandra Mazzeo; Antonio De Cristofaro (Veterinary Sciences, 2022)
The balance of the gut microbiome is important for the honey bee’s growth and development, immune function and defense against pathogens. The use of a beneficial bacteria-based strategy for the prevention and biocontrol of American foulbrood (AFB) and European foulbrood (EFB) diseases in honey bees offers interesting prospects. Lactic acid bacteria (LAB) are common inhabitants of the gastrointestinal tract of the honey bee. Among LABs associated with bee gut microbiota, Lactiplantibacillus plantarum (previously Lactobacillus plantarum) and Apilactobacillus kunkeei (formerly classified as Lactobacillus kunkeei) are two of the most abundant species. In this study, four Lactiplantibacillus plantarum strains and four Apilactobacillus kunkeei strains, isolated from the gastrointestinal tract of honey bee (Apis mellifera L.) were selected for their in vitro inhibition ability of Paenibacillus larvae ATCC 9545 and Melissococccus plutonius ATCC 35311. In addition, these LABs have been characterized through some biochemical and functional characteristics: cell surface properties (hydrophobicity and auto-aggregation), carbohydrates assimilation and enzymatic activities. The antimicrobial, biochemical and cell surface properties of these LABs have been functional to their candidature as potential probiotics in beekeeping and for the biocontrol of AFB and EFB diseases.